(untitled) (Journal of Finance, Business and Management Studies, 2024)
There has been a turbulent history of crises and upheavals in the banking industry, interspersed by moments of innovation. This paper examines the complex relationship between banking crises and innovation, looking at how these crises have sparked advances in banking actions, regulations, and technology. This conceptual paper explores few particular instances, notably the 2008 financial crisis and the 2023 banking crisis, along with how these acted as catalysts for reforms and inventions like fintech solutions. These developments attempted to strengthen risk management and transparency while resolving the weaknesses and vulnerabilities revealed by the crises. The paper explores how credit risk assessment and fraud detection are being revolutionised by data analytics, machine learning, and artificial intelligence, making banks more resilient to economic fluctuations. The role of regulatory authorities in promoting innovation and balancing it with stability is examined. In the aftermath of the banking crises, customer requirements and tastes have changed, since people are increasingly turning to digital banking and mobile payment options as they look for ease, security, and candour in their financial dealings. The obstacles and challenges of innovation in addition to its benefits are also examined. The banking industry faces serious risks from cybersecurity attacks and data breaches, necessitating constant improvements in security measures. In conclusion, there is a complicated and dynamic relationship between banking crises and innovation. Thus, in a constantly shifting financial landscape, novelty in banking must be backed by cautious risk assessment and a solid regulatory environment, in order to preserve the stability and resilience of this sector.